The Concept of Integration of Legal Knowledge and Skills in the Implementation of MBKM at PTKIN - Chaerul Shaleh; Ridwan Eko Prasetiyo; Fitri Febriani wahyu (UIN Sunan Gunung Djati Bandung, 2026)
The Faculty of Sharia was developed on the basis of a paradigm of legal science based on values and the spirit of teachings, which is standardized through the qualifications of legal education levels, which are able to produce graduates who have academic qualifications and work skills in the legal field, this qualification standardization has an impact on the scientific structure that has been developed based on the concept of integration of science, after the implementation of MBKM, integration is continued with the achievement of work skills competencies needed in the business world and the legal industry, the purpose of this study is directed to find out: 1) Scientific Construction of the Faculty of Sharia at PTKIN, 2) Mapping the Integration of Science and Legal Skills of the Faculty of Sharia at PTKIN, 3) Design of the implementation of work internships at the faculty of sharia Through the MBKM model, the concept used in this study is the conception of integration as a model of uniting views on different elements to become a new form, in the MBKM policy integration is interpreted as link and match., this study uses an empirical juridical approach by analyzing the process of implementing integration-based education at PTKIN, while the data sources in this study are in the form of the implementation of the model of integration of science and legal skills, with a data collection model The data is obtained through interviews, observations and document analysis of the implementation of the integration model, the results of this study found; 1) the construction of legal science is based on the discipline of legal science as science (law in abstrakto), and the science of methodology to solve legal problems (law in congcrito), 2) The concept of integration means combining knowledge and skills, 3) The plan for implementing MBKM at the Faculty of Sharia within the PTKIN environment is planned to be followed by 42 religious universities, with 10 types of study programs participating, with the number of courses offered being 1,436 courses.